Enhanced extraction performance of iridoids, phenolic acids from Eucommia ulmoides leaves by tailor-made ternary deep eutectic solvent - Yu, Lian; Cao, Liu; Chang, Yuan-Hang; Duan, Cong-Jia; Liu, Chang; Zhao, Xue-Lian; Yue, Gan-Lu; Wang, Xi-Qing; Fu, Yu-Jie (Microchemical journal, 2021)
•A novel TDES was firstly applied to extract bioactive compounds from EUL.•Ascorbic acid was evaluated as the HBD2 of TDES to improve extraction performance.•The bioactive compounds extraction yields of ternary DES was higher than binary DES.•The excellent recovery TDES and high activity of extract were obtained. In this work, an efficient and environmentally friendly extraction process was proposed to simultaneously obtain iridoids and phenolic acids from Eucommia ulmoides Oliver leaves (EUL). Namely, the integrated microwave-assisted ternary deep eutectic solvent extraction (TDES-MAE), which was firstly applied to extract compounds from EUL for the first time. In the tailor-made TDES system, tiny ascorbic acid (Vc) was added to modify the acidity of the binary deep eutectic solvents (BDES)composed of a 1:2 M ratio of Choline chloride/1,4-butanediol)to form TDES, which possess a higher extraction yield than BDES. Some factors including DES types, molar ratio, water content and selection of hydrogen bond donor (HBD) were investigated to get the superior TDES solvent. Then Box-Behnken design was implemented to acquire the optimum conditions, such as extraction time, extraction temperature, liquid-solid ratio were optimized by using response surface methodology (RSM). Under the optimal conditions, extraction efficiency of the TDES-MAE was significantly increased and 1.4-fold to the traditional method. Meanwhile, the excellent recovery and the antioxidant activity shown that the extraction system based on tailor-made TDES was economically productive and efficient for extracting more beneficial products from plants.